Freedom of Speech and Expression versus the glorification of acts of terrorism: Defining limits in the Indian context - Chadha, Vaibhav (The Age of Human Rights Journal, 2021)
Freedom of speech and expression is one of the essential rights for humans; however, some people in the guise of right to freedom of speech and expression glorify the acts of terrorism. In India, there are several laws making certain speeches punishable, but these laws fail to take into consideration speeches that glorify terrorists or acts of terrorism. The objective of this article is to examine the scope of provisions or laws that may be introduced to prohibit speech glorifying acts of terrorism in India while maintaining a balance with the right to freedom of speech and expression granted under the Constitution of India, 1950. This article attempts to assess United Nation Security Council Resolution 1624 and laws enacted in the wake of terrorist attacks in European countries such as the United Kingdom and France, and how they deal with speech that glorifies terrorism. This article also discusses case laws on glorification of terrorism of the European Court of Human Rights.